2020
DOI: 10.3390/jcm9082346
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Root-Analogue Implants Restored with Single Crowns or Fixed Dental Prostheses: A Retrospective Case Series

Abstract: The objective was to investigate clinical and radiological outcomes of rehabilitations with root-analogue implants (RAIs). Patients restored with RAIs, supporting single crowns or fixed dental prostheses, were recruited for follow-up examinations. Besides clinical and esthetical evaluations, X-rays were taken and compared with the records. Patients were asked to evaluate the treatment using Visual Analogue Scales (VAS). For statistical analyses, mixed linear models were used. A total of 107 RAIs were installed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…RAIs are de ned as implants that have the same contour as the extracted root [2,3]. Compared to traditional implants, RAIs have some advantages, such as a better t in the extraction socket, eliminating the need for conventionally used bone drills and other traumatic procedures that are required to prepare for implantation, as well as uncomplicated immediate implant placement, increased patient comfort, and better aesthetic effectiveness through immediate temporary restoration [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAIs are de ned as implants that have the same contour as the extracted root [2,3]. Compared to traditional implants, RAIs have some advantages, such as a better t in the extraction socket, eliminating the need for conventionally used bone drills and other traumatic procedures that are required to prepare for implantation, as well as uncomplicated immediate implant placement, increased patient comfort, and better aesthetic effectiveness through immediate temporary restoration [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Although many researchers had reported many successful clinical cases using RAIs in the past years [6,9], there have been some failures [8,10]. Research has shown that stress distribution in the bone around implants under loading is related to the success of implantation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many researchers have reported the successful use of RAIs in clinical cases [11,15,16]. However, there have also been some cases of failure [17,18]. Evans et al [10] found that the main reason for RAI failure was pressure-induced resorption or fracture of the thin buccal wall of the alveolar bone.…”
Section: Introductionmentioning
confidence: 99%
“…Although many researchers had reported many successful clinical cases using RAIs in the past years [ 6 , 9 ], there have been some failures [ 8 , 10 ]. Research has shown that stress distribution in the bone around implants under loading is related to the success of implantation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…RAIs are defined as implants that have the same contour as the extracted root [2,3]. Compared to traditional implants, RAIs have some advantages, such as a better fit in the extraction socket, eliminating the need for conventionally used bone drills and other traumatic procedures that are required to prepare for implantation, as well as uncomplicated immediate implant placement, increased patient comfort, and better aesthetic effectiveness through immediate temporary restoration [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%